When Dispute Threatens Harmony in the Public Sphere: Discerning the Dynamics of State-Religion Relation with Particular Reference to Singapore's Muslim Scholars - Bin Md Aris, Mohd Murat (Department of Religious Studies, 2023)
Islamic religious contestation is not new in Singapore. Its roots took shape during the formative years of early Singapore when Islam came to its shores on the waves of trade and migration. However, over the years, the contestation was characterized by new dynamics, chief of which were secularization, globalization, information technology, and the increasing multi-racial and multi-religious character of its population. In this evolving environment, state and religious authorities are constantly subject to challenges, especially when the ubiquitous presence of social media enables the independent acquisition of Islamic understanding, bypassing traditional Islamic hierarchies. Globalization poses challenges to established traditional religious leaders, as well as to state-religion relations and management in Singapore. In this contestation, new Islamic religious authorities are emerging and adapting. In Weber's sense, one group called the traditional, supports the status quo, while another two groups, namely the Salafis and Sufis, challenge established norms and traditions. These new religious actors vie for authority and authenticity, pitting themselves against each other and the state authorities. There is increasing concern that the contestation is spilling over into the public spheres and threatens to unravel the social contract of co-existence and harmonious living in Singapore. In studying religious contestation in Singapore, my study has used Weber and Whitehouse's theoretical concepts to analyze how religious leaders transmit the knowledge of Islam. Charisma, in Weber's sense, plays a destabilizing role in the religious sphere. In this study, religious leaders on all sides display charismatic qualities in attracting followers. Moreover, I show that charisma is created through what Whitehouse has called modes of transmission. Using a range of doctrinal and imagistic modes of delivery, religious leaders attract and keep their followers. While leaders who are part of the religious establishment tend to use doctrinal modes of transmission, they are not averse to using imagistic modes as well. The new leaders that challenge the status quo tend to use imagistic modes of delivery, but they are not shy about exploiting doctrinal modes of delivery as well. I found generally, both modes serve the charismatic attraction of Singaporeans to the third generation of religious leaders who attend their meetings, follow them on Facebook and read their books.